Determination of chlorpheniramine enantiomers in pharmaceutical formulations by HPLC on chiral column with PDA detection - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2020)
Background and Aims: An HPLC method with photodiode array detector on a chiral column was proposed for enantioselective determination of chlorpheniramine (CLP) enantiomers in dosage forms. Methods: The enantioselective determination was achieved on amylose tris(3,5-dimethylphenylcarbamate) column, using n-hexane-(propan-2-ol)-diethylamine (97.5:2.5:0.025, v/v/v) mobile phase. The peaks were detected at 258 nm. Diphenhydr amine was used as an internal standard (IS). A new sample preparation procedure was developed to avoid the interference of the other ingredients present in the formulations. Results: Limit of quantification of the proposed method was 0.88 and 1.31 mu g/mL for S-(+)-CLP and R-(-)-CLP, respectively. Conclusion: The method is linear, sensitive, specific and can be used for the enantioselective assay of CLP enantiomers in pharmaceutical formulations.
Keywords: Chlorpheniramine; amylose tris(3; 5-dimethyl phenylcarbamate); enantioselective determination; HPLC-PDA; chirality